Effect of Functionally Graded Material of Disc Spacer with Presence of Multi-Contaminating Particles on Electric Field inside Gas Insulated Bus Duct - Mousa Awad Allah Abd Allah; Sayed Abo El Saood Ward; Amr Ameen Youssef (International Journal of Electrical and Computer Engineering (IJECE), 2013)
Solid insulators play a crucial role of electrical insulation in gas insulated power equipment. In order to improve the insulation performance of the solid insulators, two technical points should be considered, the first is the improvement of the insulation performance and the second is the control of the electric field distribution in and around the solid insulating spacers. Practically the insulation performance around the spacer can be improved by various techniques, such as; controlling the spacer shape, adding shield electrodes for electric field relaxation, the introduction of an embedded electrode, etc. These techniques lead to a more complicated structure of the equipment and increase the manufacturing cost. Thus, it is necessary to propose a new concept on solid spacers with keeping their simple structure and configuration. In this paper, a functionally graded material (FGM) is proposed to minimize the electric field distribution around the spacer, specially, on triple junction point, which was one of the important factors dominating a long-term insulating property of solid delectric. Finite Element Method (FEM) has been used throughout this work, for its favorable accuracy, to calculate the electric field distribution inside the bus duct. The Electric field distribution around earthed particle contamination which adhered to uniform and FGM of disc-spacer is presented. The effect of distance between particle and spacer on the electric field values is investigated. The effect of hemi-spherical radius and length of particle on maximum electric field at triple junction point is also discussed. Electric field relaxation effect (EFGM/Euniform) by introduction of the U-shape FGM spacer is also presented. The electric field distribution along the surface of FGM of disc spacer with presence of multi-contaminating particles at various positions is presented.DOI:http://dx.doi.org/10.11591/ijece.v3i6.4354